Electric circuit modelling for lithium‐ion batteries by intermittent discharging. Issue 10 (1st October 2014) - Hsieh, Yao‐Ching; Lin, Tin‐Da; Chen, Ruei‐Ji; Lin, Hong‐Yu
Abstract : This study introduces a battery modelling technique for lithium‐ion batteries. Repeated intermittent discharging experiments are performed on batteries for a lot of times, and followed by analyses on the battery terminal voltage curves to find an appropriate battery model based on circuit elements and the equations of the battery model parameters. The proposed model is verified by simulating the battery voltages under discharging with different currents. Dynamic behaviours of the battery can be predicted by this model. It can be expected furthermore, real‐time state‐of‐charge estimation algorithm maybe developed by using this model.